ABUNDANCE AND DIVERSITY OF BIRD SPECIES AND THEIR CONSERVATION STATUS IN THE COASTAL AREA AND MARANA RIVER ESTUARY, MAROS REGENCY - Baharuddin, Nur Ulfah; Burhanuddin, Andi Iqbal; Priosombodo, Dody; Niartiningsih, Andi (Hasanuddin University, 2024)
Marana river estuary and its surrounding coastal area have been converted into extensive fishpond. This muddy environment with abundant fish in shallow waters, mangroves and Nypa palm attracts various species of birds to forage for food. This area also visited by migratory birds. However, avifauna in this area still poorly studied. Based on this, research on abundance, diversity of bird species and its conservation status was conducted. The aim of this study was to determine the abundance, ecological index and conservation status/protection status of bird species in coastal and estuary of Marana River, Maros Regency. Totally, six stations were set up in three different habitat types. Two stations were placed in the mangrove area around the mouth of the river, two stations in the pond area next to the river and two stations in the middle of the river that entered further inland. Data was collected using the point count method, with 3 replicates of different observation points set up randomly at each station. Each point has a circular observation area with a radius of 50m. The distance between observation points is 300m with a bird watching time of 20 minutes at each observation point. Bird species outside the observation area were also recorded but not counted. From the observations, a total of 22 bird species from 14 families were recorded from all stations. Most of the bird species dominated by waterbirds and open country specialized birds i.e: Whiskered Tern (Dara-laut Kumis), Glossy Swiftlet (Walet Sapi) and Little Egret (Kuntul Kecil). From ecological index analysis, bird community in all stations is categorized as stable, with moderate diversity, low dominance and high eveness index except for station 2 which is mostly dominated by Whiskered Tern. All bird species conservation status is categorized as Least Concern (LC) by IUCN. Little Egret (Kuntul Kecil), Cattle Egret (Kuntul Kerbau) and Great Egret (Kuntul Besar) are included in appendix III CITES. Furthermore, four shorebird species: Far Eastern Curlew (Gajahan Timur), Eurasian Whimbrel (Gajahan Pengala), Whiskered Tern (Dara-laut Kumis) and White-winged Tern (Dara-laut Sayap Putih) are protected by the Indonesian Government. It is concluded that bird communities in study sites are stable and Marana estuary can still support bird life, especially for migratory and protected bird species.